2020
DOI: 10.1155/2020/8294560
|View full text |Cite
|
Sign up to set email alerts
|

New Potential Weapons for Refractory Scleritis in the Era of Targeted Therapy

Abstract: Objective. To assess the efficacy of biologic drugs, beyond tumor necrosis factor- (TNF-) α inhibitors, in the management of noninfectious refractory scleritis, either idiopathic or associated with systemic immune-mediated disorders. Patients and Methods. This is a retrospective study assessing the efficacy of several biologic agents (rituximab, anakinra, tocilizumab, and abatacept) and the small molecule tofacitinib in the treatment of scleritis through assessment of scleral inflammation and relapses, as well… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 17 publications
1
17
0
Order By: Relevance
“…A total of 85.5% (71/83) reported no adverse events following treatment with RTX for non-infectious scleritis. However, two patients each (2/83, 2.4%) developed itching with infusion [ 70 ] and disease exacerbation [ 58 , 62 ], and one patient each (1/83, 1.2%) developed herpetic mouth ulcers [ 37 ], acute retinal necrosis [ 67 ], herpes zoster [ 56 ], hypotension during infusion of RTX [ 55 ], ocular hypertension [ 57 ], pneumonia with septic shock [ 60 ], dry eyes, the combination of weight loss, fatigue, and joint pain [ 63 ], and the combination of leukopenia, anemia, bronchitis, and bacterial pneumonia [ 56 ] attributed to RTX treatments.…”
Section: Resultsmentioning
confidence: 99%
“…A total of 85.5% (71/83) reported no adverse events following treatment with RTX for non-infectious scleritis. However, two patients each (2/83, 2.4%) developed itching with infusion [ 70 ] and disease exacerbation [ 58 , 62 ], and one patient each (1/83, 1.2%) developed herpetic mouth ulcers [ 37 ], acute retinal necrosis [ 67 ], herpes zoster [ 56 ], hypotension during infusion of RTX [ 55 ], ocular hypertension [ 57 ], pneumonia with septic shock [ 60 ], dry eyes, the combination of weight loss, fatigue, and joint pain [ 63 ], and the combination of leukopenia, anemia, bronchitis, and bacterial pneumonia [ 56 ] attributed to RTX treatments.…”
Section: Resultsmentioning
confidence: 99%
“…4,6,7,16 In our series, the prevalence of these autoantibodies was slightly higher than previously reported. [17][18][19] This finding may be partly due to our tertiary referral center specialized in immunological disorders, or might in part be attributable to the use of different, more sensitive laboratory techniques for autoantibody detection.…”
Section: Discussionmentioning
confidence: 99%
“…In 2010, Iaccheri et al reported a case of acute stromal keratitis and scleritis, with only partial response to cyclophosphamide, who was successfully controlled after two infusions of rituximab, off all steroids and without recurrence after 9 months of follow-up [ 25 ]. In the retrospective series of Fabiani et al, 4 out of 5 patients treated with rituximab improved by at least 2 step of scleritis grading system [ 30 ]. Adverse effects may include reactivation of viruses, as reported with acute retinal necrosis [ 31 ].…”
Section: Treatment Modalities and Perspectivesmentioning
confidence: 99%
“…Tocilizumab was reported effective to control inflammation and steroid sparing in 50% of patients with refractory scleritis [ 36 ]. In the retrospective series of Fabiani et al [ 30 ], 2 patients (3 eyes) were successfully treated with 162 mg/week of tocilizumab and 3 patients (4 eyes) treated for diffuse anterior scleritis, 2 patients (2 eyes) were successfully controlled with 125 mg weekly abatacept.…”
Section: Treatment Modalities and Perspectivesmentioning
confidence: 99%
See 1 more Smart Citation